Constructions of Spartan masculinity in Classical Athenian prose - Heydon, Kendell A. (2018)
Employing a methodological approach informed by sociological social constructionist theories of gender, I endeavour to explore representations of Spartan masculinity in the works of Xenophon Thucydides and Plato, to gain better understanding of portrayals and usages of ideologies of Spartan masculinity in Classical Athenian philosophical and historical works. I structure my project by focusing on seven categories which constructionists believe to be important to the formation of masculinity. My aim is to demonstrate the utility of this methodological framework for exploring historical masculinities and to contend that there is no singular representation of Spartan masculinity within Classical Athenian prose. Rather, representations of Spartan masculinity are complex and multifaceted, with authors constructing and employing different ideologies of Spartan masculinity situationally and for a variety of purposes, both internal and external to the texts.